To make $\displaystyle i$ the subject of the following equation, these are my workings

$\displaystyle r=[1+i/12]^{12}-1$

1. Add 1 to both sides

$\displaystyle r+1=[1+i/12]^{12}$

2. Open the brackets so that

$\displaystyle r+1=1+i^{12}/12^{12}$

3. Then multiply both sides by $\displaystyle 12^{12}$ to give

$\displaystyle 12^{12}(r+1)=1+i^{12}$

4. And then finally

$\displaystyle 12^{1/12}(r+1)-1=i$

The answer in the book though is

$\displaystyle 12((r+1)^{1/12})-1=i$

But I don't understand why I was supposed raise$\displaystyle (r+1)$ to the power of 12 when I multiplied by $\displaystyle 12^{12}$ in step 3